2001
DOI: 10.1002/ijc.1278
|View full text |Cite
|
Sign up to set email alerts
|

Cohort analysis of fruit and vegetable consumption and lung cancer mortality in European men

Abstract: Our aim was to examine the relationship between fruit and vegetable consumption and lung cancer mortality in a cohort of European males. Around 1970, dietary intake of Finnish, Italian and Dutch middle-aged men was assessed using a cross-check dietary history. Complete baseline information was available for 3,108 men, of whom 1,578 were baseline smokers. We used Cox proportional hazard analyses to calculate risk estimates for the consumption in country-specific tertiles on lung cancer in smokers. During 25 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 31 publications
1
17
2
Order By: Relevance
“…Several studies have indicated a protective effect of fruits and vegetables on lung cancer risk among current smokers only (24,29,30). It is argued that the inverse association among current smokers seen in some studies might be due to residual confounding by smoking (25).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated a protective effect of fruits and vegetables on lung cancer risk among current smokers only (24,29,30). It is argued that the inverse association among current smokers seen in some studies might be due to residual confounding by smoking (25).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is the highest risk factor for lung carcinoma, but exposure to asbestos, radon, and other airborne carcinogens play a role, along with diet. 53 Although the higher mortality rates from lung carcinoma reported in the southeast U.S. for white Americans are not surprising because the majority of the tobacco in the U.S. is grown in the south and the smoking rates tend to be higher there, 54,55 the lower rates of lung carcinoma mortality reported for black Americans in the southeast states compared with the states to the north are surprising. The finding that there is a strong inverse correlation between lung carcinoma mortality rates and solar UV-B radiation for this group, if indeed related to a protective effect of solar UV-B radiation, most likely is associated with a nearly uniform rate of smoking among black Americans throughout the eastern U.S.…”
Section: Discussionmentioning
confidence: 99%
“…For 11 cohort studies on vegetable consumption (74, [119][120][121][122][123][124][125][126][127][128], the mean relative risk was 0.80 and the range was 0.47-1.37 (Fig. 19).…”
Section: Lungmentioning
confidence: 99%